The efficacy of law enforcement in the Tolaki Mekongga Indigenous Law Community's adultery (Umoapi) resolution process - Hasdin Yadin; Haeranah Haeranah; Hijra Adhiyanti Mirzana (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The purpose of this study is to ascertain and analyze the mechanism for resolving the crime of adultery (Umoapi) in the Tolaki Mekongga customary law community, as well as the efficacy of law enforcement in resolving the crime of adultery (Umoapi). The research method utilized is empirical, with data gathering approaches including interviews, questionnaires, and document studies, in which data are extracted directly from documents containing information about the study topics, such as laws and regulations, books, and journals. The findings indicated that (1) the mechanism for resolving adultery (Umoapi) in the Tolaki Mekongga customary law community was through the imposition of customary penalties by customary speakers (tolea), and (2) law enforcement was successful in resolving adultery (Umoapi) in the community. Tolaki Mekongga customary law is influenced by elements like as law, law enforcement, facilities and infrastructure, community, and cultural influences.